Ethical Leadership and Follower Moral Actions: Investigating an Emotional Linkage - Zhang, Yajun; Zhou, Fangfang; Mao, Jianghua (Frontiers in Psychology, 2018)
The effectiveness of ethical leadership has been extensively investigated. However, compared to the outcomes of ethical leadership, we still lack enough knowledge about the mechanisms underlying ethical leadership and its outcomes. Drawing from social information processing theory, this paper explores an emotional explanation for the effectiveness of ethical leadership. Adopting a time-lagged research design with responses from 64 leaders and 289 followers, the present research found that ethical leadership invokes followers’ other-praising emotions and eventually enhances their moral actions. Further, leader core self-evaluation contributes to the positive effects of ethical leadership on followers’ other-praising moral emotions and subsequent moral actions. Theoretical and practical implementations of these observations were discussed.